Two distinct auto-regulatory loops operate at the PU.1 locus in B cells and myeloid cells - Leddin, Mathias; Perrod, Chiara; Hoogenkamp, Maarten; Ghani, Saeed; Assi, Salam; Heinz, Sven; Wilson, Nicola K; Follows, George; Schönheit, Jörg; Vockentanz, Lena; Mosammam, Ali M; Chen, Wei; et al. (Blood, 2011)
The transcription factor PU.1 occupies a central role in controlling myeloid and early B-cell development, and its correct lineage-specific expression is critical for the differentiation choice of hematopoietic progenitors. However, little is known of how this tissue-specific pattern is established. We previously identified an upstream regulatory cis element whose targeted deletion in mice decreases PU.1 expression and causes leukemia. We show here that the upstream regulatory cis element alone is insufficient to confer physiologic PU.1 expression in mice but requires the cooperation with other, previously unidentified elements. Using a combination of transgenic studies, global chromatin assays, and detailed molecular analyses we present evidence that PU.1 is regulated by a novel mechanism involving cross talk between different cis elements together with lineage-restricted autoregulation. In this model, PU.1 regulates its expression in B cells and macrophages by differentially associating with cell type-specific transcription factors at one of its cis-regulatory elements to establish differential activity patterns at other elements.